Fresno County Counsel Softball Team and Office BBQ at Wes Merritt's Backyard - Watkins, Howard::::::::: (1987)
Pamela Stone laughing, Phil Jay; background: Maureen Walsh, Jane Kuhn holding baby, Jeff Kuhn, ?